2022
DOI: 10.1369/00221554221101661
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Redistribution of Left Ventricular Connexin 43 Contributes to the Remodeling of Electrical Properties of the Heart in Insulin-resistant Elderly Rats

Abstract: The correlation between long-QT and connexin 43 (Cx43) status and localization in elderly rats was determined to demonstrate a correlation between insulin resistance (I-R), ischemia-reperfusion, aging, and heart dysfunction. Male Wistar rats are grouped as 24-month-old rats (Aged-group), those with metabolic syndrome (8 months old; MetS-group), or controls (8 months old; Con-group). Both experimental groups have long-QT and low heart rate. Immunohistochemical imaging and quantification showed marked decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 93 publications
(111 reference statements)
1
6
4
Order By: Relevance
“…Representative histological microphotographs associated with Cx43 are given in Figure 5A. Opposite to our previous study performed in the late‐stage MetS rats, 26 we, here, observed an unchanged Cx43 expression level in the heart the MetS rats compared to the CON group of rats CON (Figure 5C). This is followed by a marked increase in its intercalated discs (ID) localization as shown by high‐density Cx43 immunostaining in the samples from the MetS rat hearts, whereas its immunostaining along the longitudinal cell membrane (LCM) showing its lateralization was not different from the CON group rats with a less immunostaining level in the cytoplasm (less internalization of Cx43).…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Representative histological microphotographs associated with Cx43 are given in Figure 5A. Opposite to our previous study performed in the late‐stage MetS rats, 26 we, here, observed an unchanged Cx43 expression level in the heart the MetS rats compared to the CON group of rats CON (Figure 5C). This is followed by a marked increase in its intercalated discs (ID) localization as shown by high‐density Cx43 immunostaining in the samples from the MetS rat hearts, whereas its immunostaining along the longitudinal cell membrane (LCM) showing its lateralization was not different from the CON group rats with a less immunostaining level in the cytoplasm (less internalization of Cx43).…”
Section: Resultssupporting
confidence: 56%
“…The left ventricles were isolated to perform routine histological procedures, as described previously 26 . Briefly, the tissue samples were fixed in phosphate‐buffered 10% formalin for 96 h and then dehydrated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations